Thistle Control in Pastures - Brent Sellers; Jason Ferrell; Curtis Rainbolt (EDIS)
SS-AGR-95, a 3-page illustrated fact sheet by Brent Sellers, Jason Ferrell, and Curtis Rainbolt, provides information on the biology and control of thistle in pastures. Includes an identification key and herbicide recommendations. Published by the UF Department of Agronomy, May 2006. Reviewed November 2006.